The unity of general didactic principles in the process of formation linguistic and speech competences with students of primary and secondary school - Yavorska, Stefaniia (Pedagogical Discourse, 2018)
The article is devoted to the problem of formation linguistic and speech competences with students of primary and secondary school on the basis of the application of general didactic principles of activity, consciousness, self-dependency, progressive movement, sequence, perspectiveness, simplicity, connection of theory and practice, scientific principle, systemic principle. The author’s methodology on learning theoretical material, enriching students’ vocabulary and developing communicative skills is based on the analysis of scientific sources and presupposes a complex approach to teaching taking into account the initial level of knowledge and development of students. The actuality of the investigated problem is grounded; the factors which stipulate the realization of didactic principles are determined. It is proved that to master rules easily and to spare time on practical exercises it is necessary to use knowledge acquired by students in the way it (knowledge) can become a scaffold for the material which will be worked through next year. The methods of work on the actualization of students’ knowledge in complex is defined; the effectiveness of this teaching is proved. It is reasoned that a scaffold on all needed earlier learned rules requires from a teacher the utilization of effective methods and techniques of work that will depend on the knowledge of students, the class potential; the conditions under which the teacher will conduct a class. For the consolidation of linguistic material with due regard for knowledge and age peculiarities of students it is recommended to select texts, to use proverbs, sayings, poems, different dictations, narrations, fragments of fiction, artistic miniatures and so on. The conclusion is made that a capable utilization of didactic principles activates the learning process of students, favors the strength of knowledge, develops logical memory, makes the process of learning interesting. Various forms of work with a text ensures that students master all types of oral and written speech.